Predicting the settlement of footings on sand using a bounding surface plasticity model - Hughes,T; Taborda,DMG; Zdravkovíc,L; Potts,DM (Taylor and Francis - Balkema, 2014)
Despite having been the subject of extensive research, the prediction of load-settlement response of footings on sand deposits currently yields relatively poor and unreliable results. This paper aims at providing insight into this problem by examining the ability of a bounding surface plasticity model to predict the response of four distinct footings on Perth sand, which were tested as part of an international prediction event. Given the complexity of the chosen constitutive model and the relatively limited ground information available, emphasis is placed on the calibration procedure. In particular, the contributions of specific components of the constitutive model, such as the ability to simulate stiffness degradation at small deformation levels and the adopted formulation for the plastic hardening modulus, are investigated in a parametric study. Axisymmetric finite element analyses demonstrate that the response of the footings measured in the field is adequately simulated using the selected constitutive model. © 2014 Taylor & Francis Group.